PENERAPAN KONSEP GREEN TOURISM DALAM PENGEMBANGAN PANTAI KELAN TUBAN SEBAGAI DAYA TARIK WISATA BERKELANJUTAN DI KABUPATEN BADUNG - Putu Agus Prayogi; I Wayan Kartimin; I Made Hedy Wartana (Journal of Tourism and Interdiciplinary Studies, 2022)
Kelan Beach is one of the tourist attractions that until now has become a tourist location that is crowded with local and foreign tourists. Tourism is an attraction for tourists visiting Kelan Beach. The problem encountered in this research is that there is no accommodation or tourist attraction so that tourism in Kelan Beach has not developed well and the role of stakeholders in tourism development on Kelan Beach has not been carried out in accordance with the main objectives. This problem will be discussed using the SWOT analysis technique. This research is a qualitative research supported by the types of data and data sources, namely qualitative data and quantitative data as well as primary and secondary data. Data collection techniques used are observation, interviews, questionnaires and documentation. The data analysis technique used is the SWOT analysis technique, namely analyzing internal factors (strengths and weaknesses) and external factors (opportunities and threats) with the help of the Internal-External matrix and the SWOT matrix. In implementing the strategy for developing Kelan Beach as a sustainable tourist attraction, it also applies the principles of Green Tourism which lead to environmental preservation. With the condition of Kelan Beach where the environment still tends to be natural, the application of the principles of environmental preservation is a must. Preservation of the environment around Kelan Beach must involve the local community, government, businessmen and visiting tourists. The government, both regional and village governments, is obliged to issue a policy regarding environmental management around Kelan Beach which is based on the principle of preservation. Communities, entrepreneurs and tourists participate in supervising its implementation and are directly involved in preserving the environment around Kelan Beach. This is very important to implement so that tourism on Kelan Beach can be sustainable